2011
DOI: 10.1002/cncr.25830
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical subtyping of nonsmall cell lung cancer not otherwise specified in fine‐needle aspiration cytology

Abstract: BACKGROUND: Histopathological subtyping of nonsmall cell lung cancer (NSCLC) is currently relevant in treatment decision because of a differential activity of specific therapeutic agents. Immunohistochemistry highlights cell differentiation lineages and, in this study, it was applied to maximize the proportion of accurately subtyped NSCLC not otherwise specified (NOS) on fine-needle aspiration cytology (FNAC) samples. METHODS: Cell blocks from 103 FNAC samples with a morphological diagnosis of NSCLC-NOS were i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

12
133
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 134 publications
(147 citation statements)
references
References 27 publications
12
133
2
Order By: Relevance
“…However, recent immunohistochemical studies that have focused on poorly differentiated non-small cell carcinomas in small biopsies or cytology specimens with resected tumors as the gold standard have shown that some markers, especially when used in combination, are indeed useful and accurate in subclassifying poorly differentiated non-small cell lung carcinomas. [5][6][7][8] As subclassification using these markers shows excellent correlation with the gold standard H&E-based diagnosis on resected tumors, immunohistochemistry has become accepted as a reliable technique for subclassification when diagnostic features on H&E morphology are absent in a small biopsy. To summarize the current state of non-small cell lung carcinoma subclassification, H&E-based criteria remain the gold standard for subclassifying resected tumors.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, recent immunohistochemical studies that have focused on poorly differentiated non-small cell carcinomas in small biopsies or cytology specimens with resected tumors as the gold standard have shown that some markers, especially when used in combination, are indeed useful and accurate in subclassifying poorly differentiated non-small cell lung carcinomas. [5][6][7][8] As subclassification using these markers shows excellent correlation with the gold standard H&E-based diagnosis on resected tumors, immunohistochemistry has become accepted as a reliable technique for subclassification when diagnostic features on H&E morphology are absent in a small biopsy. To summarize the current state of non-small cell lung carcinoma subclassification, H&E-based criteria remain the gold standard for subclassifying resected tumors.…”
mentioning
confidence: 99%
“…Furthermore, although napsin A is slightly less sensitive for poorly differentiated adenocarcinomas than TTF-1, it is valuable in occasional adenocarcinomas that are napsin A-positive but TTF-1-negative. [8][9][10] Finally, napsin A stains adenocarcinomas but not small cell carcinomas, 9 a fact that can be helpful when the differential diagnosis of a TTF-1-positive poorly differentiated carcinoma includes small cell carcinoma. Similarly, although p63 is more sensitive for squamous cell carcinomas than CK5/6, the latter is useful when p63 staining is focal, weak or equivocal.…”
mentioning
confidence: 99%
“…Although the optimal diagnostic algorithm is not firmly established, recent studies show that immunohistochemistry increases accuracy and reproducibility, and minimizes the rate of non-small cell carcinoma-not otherwise specified diagnoses in small specimens. [13][14][15][16][17] We recently showed that the rate of adenocarcinoma and squamous cell carcinoma unclassified by preoperative cytology in clinical practice with routine utilization of immunohistochemistry is low (3%). 18 Common markers used for non-small cell carcinoma subtyping include TTF-1 for adenocarcinoma vs p63 and high-molecular weight keratins (CK5/6 and 34bE12/CK903) for squamous cell carcinoma.…”
mentioning
confidence: 99%
“…Given the recent insights into the clinical and biological significance of non-small cell carcinoma subtypes, several recent studies have analyzed the utility of various combinations of markers for the distinction of adenocarcinoma and squamous cell carcinoma. These studies were performed in small biopsies, [14][15][16] cytology, 17,23 and tissue microarrays, [24][25][26] and the proposed algorithms include between fourand six-marker panels. Although most studies agree on the inclusion of TTF-1 and p63 in the panel, there is no agreement on the role of additional markers.…”
mentioning
confidence: 99%
“…26 In the majority of pathology laboratories, the routine p63 antibody is 4A4, which recognizes both TAp63 and DNp63 isoforms. The p40 antibody, which exclusively recognizes the DNp63 isoform, may have a superior specificity 29 but inferior sensitivity [30][31][32] compared with p63 in the diagnosis of pulmonary SqCC.…”
Section: Primary Epithelial Tumors Of Lungmentioning
confidence: 99%